STUDIES ON BACTERIAL NUTRITION : III. PLANT TISSUE, AS A SOURCE OF GROWTH ACCESSORY SUBSTANCES, IN THE CULTIVATION OF BACILLUS INTLUENZÆ. - Thjötta, Theodor (The Rockefeller University Press, 1921)
1. Growth of Bacillus infiuenzœ depends on two distinct and separable substances. 2. These growth accessory substances are present in blood. 3. They occur in plant as well as in animal tissue. 4. Sterile, raw potato will serve as a substitute for blood in the cultivation of Bacillus influenzœ.